Laboratory Bioassay of some Insecticides as Contact Poison against Third Instar Larvae of Glyphodes pyloalis Walker (Lepidoptera : Pyralidae) - Gupta, B. K.; Veer, Vijay (Indian Forester, 1986)
The nineteen conventional insecticides were tested as contact poison against third instar larvae of Glyphodes pyloalis in laboratory. The descending order of toxicity of the insecticides was : chlordimeform> formotbion > quinalphos >monocrotophos> toxaphene> carbaryl> fenitrothion> malathion (premium grade) :> methyl parathion > endosulfan > malathion + fenitrotbion > leptophos :> klofos :>dichlorvos > endosulfan > DDT > dimethoate> pyretbrum>chlordane>gamma-BHC. Monocrotophos, formothion and chlordimeform are 27 to 32 times more toxic than DDT. Relative resistance to these insecticides of Glyphodes pyloalis than Selepa celtis is also discussed.